EVOLUTION OF THE EAST SYRIAC INITIATION SETUP WITH STRUCTURE AND THEOLOGY - Moolan, John (Asian Horizons, 2016)
East Syrians are Chaldeans, Assyrians, and Syro-Malabarites. Apparently, up to the fourth century, the whole Christendom kept up the integrity of the sacraments of initiation (Baptism, Chrismation, and Eucharist) intact. Later, the West abandoned the integral administration of them due to historical and cultural reasons; but the East has always kept up their strict link. East Syrians up to the sixth century had the practice of adult initiation where the chrismatic anointing was done before baptism and Eucharist. This was in imitation of the ancient apostolic tradition of conferring the Holy Spirit first and then the baptism without any post-baptismal anointing (Acts 2:37-42; 10:44-48). Clear evidences to this effect are found in the Acts of Thomas (3rd c.) and in the works of Aphrahat (280-345), Ephrem (306-373), and Narsai (399-502). When the child initiation became very common in 6th century, Patriarch Iso-Yahb III in 7th century introduced the present child initiation rite with three anointing. In 9th century, Patriarch Elia I reformed the initiation rite of Iso-Yahb III, integrating it with the celebration of the Eucharist. Later, they developed the adult initiation in the model of child initiation, but had no much usage. This rite included a catechumenate part during the period of Great Fast and an initiation part during the paschal vigil.